Risk Factors for Contact Lens Related Microbial Keratitis - Ismail, Lili Asma (2011)
Introduction: Contact lens related microbial keratitis (CLRMK) is a complication of contact lens wear and is sight threatening. Urgent treatment is required to reduce the possibility of losing vision. A hospital case control study on the risk factors of CLRMK was conducted in seven government hospitals in the Klang Valley. Objectives:To determine the risk factors for CLRMK in relation to socio-demographics, contact lens characteristics, personal habit and contact lens care procedures in patients with CLRMK in government hospitals in the Klang Valley for the duration from January 2007 until December 2009. Materials and methods:All patients who presented with CLRMK (n=94) at the hospitals were taken as respondents. Controls (n=94) were taken from contact lens users without CLRMK. Self administered questionnaire in Bahasa Malaysia was used. The questionnaire was developed, pre-tested and validated. The clinical examinations done were visual acuity, keratometry, corneal topography and contrast sensitivity. Microbial investigations on the suspected microorganism(s) was done using culture and sensitivity. Data was analysed using SPSS 16 which included t-test, chi-square test and multiple logistic regression. Results: The most common causative agent was Pseudomonas aeruginosa with 29 (40.3%) cases isolated, followed by Serratia marcescens with six (8.3%) cases, Acanthamoeba with six (8.3%) cases, fungal with six (8.3%) cases and a mixture of several microorganisms. Higher income level per month had a lower risk for CLRMK ie RM3000-3999 [USD980-1307] (OR 0.276, CI 0.096, 0.794 p=0.017) and income level of more than RM5000 [USD1634] (OR 0.191, CI 0.063, 0.583 p=0.004), when compared to income of less than RM1000 as the referent. The risk of CLRMK was highest with monthly disposable contact lens wear (OR 7.737, CI 1.535, 38.998 p=0.001). Smoking was also a risk factor for CLRMK (OR 2.393, CI 1.021, 5.607 p=0.045). Although gender was not significantly associated with CLRMK, the frequency of CLRMK was higher in women (N=73) compared to men (N=21). Ethnicity and non-compliance contributed significantly to CLRMK. Chinese ethnicity (aOR 0.126, CI 0.045, 0.355 p=0.001) and Indian ethnicity (aOR 0.295, CI 0.088, 0.989 p=0.048) had decreased risks for CLRMK while Malay ethnicity was a predictor for CLRMK with an increased risk of 70%-87%. Non-compliance contributed to an increased risk of 2.6 times for CLRMK (aOR 2.590, CI 1.003, 6.689 p=0.049). Not washing hands with soap (aOR 2.98, CI 1.02, 8.70 p=0.046), not performing rubbing technique (aOR 3, CI 1.19, 7.54 p=0.019), not cleaning lens case with multipurpose solution (aOR 3.24, CI 1.46, 7.19 p=0.004) and sleeping in lenses (aOR 2.87, CI 0.98, 8.39 p=0.050) were identified as predictors for CLRMK. Visual acuity in the cases improved at follow up visits. However, there was a reduction in corneal uniformity index and corneal asphericity. Contrast sensitivity function at all spatial frequencies in cases was also reduced. As for the visual outcome of CLRMK, 80 respondents (85.1%) had improved visual acuity at 3 months between of 6/6 and 6/12. Five respondents (5.3%) had visual acuity between 6/18 and 6/60 while nine (9.6%) had visual acuities ranging from 6/60 to no perception of light